KORELASI KETERAMPILAN MEMAHAMI TEKS EKSPOSISI DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 PAINAN - Ena Noveria, Toto Prasetyo, Nursaid, (Universitas Negeri Padang, 2017)
This article was written to describe the relationship between the skills of reading comprehension and writing skills exposition text exposition class X SMA Negeri 1 Painan. Data were obtained through two types of tests, which is an objective test and test performance. Objective tests used to collect data reading comprehension skills exposition text, while the performance of the tests used to collect data writing skills exposition text. The results of this study there are three. First, the text reading comprehension skills exposition class X SMA Negeri 1 Painan are in qualifying Fair (C) with the average value (63.69). Second, text writing skills exposition class X SMA Negeri 1 Painan currently on qualification More than Enough (LDC) with the average value (72.08). Third, there is a significant correlation between the skills of reading comprehension skills of writing text with text exposition exposition class X SMA Negeri 1 Painan on n-1 degrees of freedom and a significance level of 0.95 for ttest> ttableÂ 2.36> 1.70.Â Kata kunci: Korelasi, keterampilan membaca pemahaman, keterampilan menulis, dan teks eksposisi